2020
DOI: 10.3390/pharmacy8010006
|View full text |Cite
|
Sign up to set email alerts
|

Checking Inhaler Technique in the Community Pharmacy: Predictors of Critical Errors

Abstract: Inhaled medications are critical in the pharmaceutical management of respiratory conditions, however, the majority of patients demonstrate at least one critical error when using an inhaler. Since community pharmacists can be instrumental in addressing this care gap, we aimed to determine the rate and type of critical inhaler errors in community pharmacy settings, elucidate the factors contributing to inhaler technique errors, and identify instances when community pharmacists check proper inhaler use. Fourth ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The present study found that MDI was the most commonly used inhaler device, followed by DPIs (Turbohaler and Diskus). Such results have been reported by previous asthma studies, specifically in Jordan 23 and worldwide 5,24,25 . Regarding MDI, our patients had poor inhaler technique; only 13.4% of MDI users used their device appropriately (had no error).…”
Section: Discussionsupporting
confidence: 87%
“…The present study found that MDI was the most commonly used inhaler device, followed by DPIs (Turbohaler and Diskus). Such results have been reported by previous asthma studies, specifically in Jordan 23 and worldwide 5,24,25 . Regarding MDI, our patients had poor inhaler technique; only 13.4% of MDI users used their device appropriately (had no error).…”
Section: Discussionsupporting
confidence: 87%
“…Cyclical training has a positive impact because pharmacists are able to refresh their knowledge and find motivation. A systematic review of effective inhalation techniques showed that the effect diminishes over time; therefore, it is important to conduct periodic training, not only for the benefit of patients but also for pharmacists [ 38 ]. Pharmacy students also have great potential.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclical training has a positive impact, because pharmacists are able to refresh their knowledge and nd motivation. A systematic review of effective inhalation techniques has shown that the effect diminishes over time, therefore it is important to conduct periodic training, not only for the bene t of patients, but also for pharmacists [35]. Pharmacy students also have great potential.…”
Section: Discussionmentioning
confidence: 99%